299 In-Depth Histological Analysis of Eosinophilic Esophagitis, With and Without Food Impaction: Outcome and Lessons Learned From 101 Adolescents. (11th January 2018) - Sonawane, Snehal; Al Rasheed, Mohamed Rizwan Haroon; Kory, Vijayalakshmi; Schwartz, Alan; Berman, James; Gunasekaran, Thirumazhisai
Abstract: Objectives: Eosinophilic esophagitis (EoE) is diagnosed with peak eosinophil count (PEC) of ≥15 intraepithelial eosinophils in at least one 40x field. Scant literature correlates additional histopathologic findings with clinical features and outcome in EoE. Our aim was to correlate 10 histopathologic criteria to clinical features, endoscopic findings, and treatment outcomes in 101 pediatric patients. Methods: EoE patients seen over a 10-year period were stratified into two groups: food-impaction (FI) n = 30 and non-Food impaction (Non-FI) n = 71. Symptoms, endoscopic (EGD) findings, and esophageal biopsies at diagnosis and follow-up were compared. Diagnosis and treatment of EoE were per consensus guidelines and clinical protocol. Symptoms were scored on a scale from 0 (absent) up to 3 (severe). Biopsies were evaluated for PEC, eosinophilic microabscesses, superficial layering of eosinophils, epithelial desquamation, basal zone hyperplasia, papillomatosis, spongiosis, fibrosis, eosinophilic degranulation, degree of involvement, and distribution of eosinophils. Non-parametric analysis and logistic regression model were utilized. Results: Mean age: 10.9 years (FI) and 10.4 years (Non-FI). Follow-up: 1.7 years (FI) and 1.1 years (Non-FI). Symptoms: For FI, dysphagia score improved, going from 3 to 1.25 ( P < .001), and composite score going from 3.28 to 1.45 ( P < .001); for Non-FI, dysphagia score improved, going from 1.21 to 0.71 ( P < .001), and mean composite score, going from 2.49 to 1.48 ( P < .001). EGD: Cumulative score improved, going from 1.8 to 1.7 in FI ( P = .70) and from 1.6 to 1.5 in Non-FI ( P = .08); PEC in FI improved, going from 60 to 27 ( P = .03), and in Non-FI improved, going from 58 to 33 ( P = .001). Additional histological features were similar in both groups at diagnosis; MAB, SLE, ED, and BZH showed linear correlation with improvement in PEC. Conclusion: Clinical features, endoscopic findings, and outcomes were similar in both groups. With treatment there was significant improvement in PEC in both groups. The 10 additional histological features were similar in both groups at diagnosis; MAB, SLE, ED, and BZH showed linear correlation with improvement in PEC.